Morphological study of chicken cecal and jejunal mucosa during epithelial cell isolation (Revista Española de Fisiología, 1986)
Epithelial cells from jejunum and proximal cecum of the chicken were isolated by using a sodium citrate containing medium.Cell dissociation during the isolation process was studied by scanning electron microscopy.Results after 5, 15 and 30 min incubation show a sequential cell detachment from the tip to the lower regions of the villi.Inspection of the cell suspension by scanning and transmission electron microscopy reveals that most cells are enterocytes that retain their characteristic cylindrical shape.The brush border of isolated cells maintains its architecture, while organelles remain intact.